Pengaruh Motivasi Kerja, Kompensasi, Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Direktorat Sarana Dan Prasarana Badan SAR Nasional - Indah Damayanti; Bulan Tati Fitria (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2018)
This research conducted at the Directorate of National SAR Agency Facilities, and Infrastructure, Results of the Preliminary Study Shows that the Employee Performance of the Directorate of National SAR Agency Facilities and Facilities is not optimal. The lack of optimal Employee Performance at the Directorate of National SAR Agency Facilities and Infrastructure is allegedly due to Work Motivation, Compensation, and Human Resource Development which are still low. Departing from the above phenomena, the problems formulated in this study are as follows: How to work motivation, compensation, human resource development, and employee performance of the Directorate of National SAR Agency's Facilities and Facilities. How significant is the influence of Work Motivation, Compensation, and Human Resource Development on the Performance of Employees of the National SAR Agency Infrastructure and Facilities Directorate both partially and simultaneously. The research method used was descriptive analysis method, with a population of 39 people, and all of them used as respondents (survey). Data analysis techniques used are correlation analysis techniques to determine the degree of closeness of the relationship between research variables and path analysis to assess the effect of both direct and indirect independent variables on the dependent variable. In its operation, SPSS 20 and Excel software used. The results showed that there was a significant effect of work motivation, compensation and development of human resources on the performance of employees of the National SAR Agency's Directorate of Facilities and Infrastructure at 80.12%.